Ovarian Reserve Markers in Premature Ovarian Insufficiency: Within Different Clinical Stages and Different Etiologies - Jiao, Xue; Meng, Tingting; Zhai, Yiwei; Zhao, Lijuan; Luo, Wei; Liu, Peihao; Qin, Yingying (Frontiers in Endocrinology, 2021)
Objective: To characterize the ovarian reserve indicators for premature ovarian insufficiency (POI) at different disease stages and with various etiologies. Methods: According to different FSH levels and menstrual conditions, patients with normal ovarian reserve (NOR with 5 IU/L